Paleomagnetic results from the Beardmore Glacier Region, Antarctica (Dataset) ... - J. C. Briden; R. L. Oliver (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic results from the Beardmore Glacier Region, Antarctica ...